Impact of soil salinity on grain yield and aromatic compound in Thai Hom Mali rice cv. Khao Dawk Mali 105 - Ayut Kongpun (2020)
Copyright © 2020. This is an open access article, production and hosting by Kasetsart University of Research and Development institute on behalf of Kasetsart University. The highest-priced aromatic Hom Mali rice is grown on saline soil in Northeast Thailand. The rice variety Khao Dawk Mali 105 (KDML 105), the main variety grown to produce Hom Mali rice was evaluated for yield, the aromatic compound 2-acetyl-1-pyrroline (2 AP) and softness texture at different levels of sodium chloride (NaCl) salt added to the soil. The rice was grown in wetland culture pots with soil made saline by adding 0 g NaCl/kg, 1.16 g NaCl/kg, 1.74 g NaCl/kg, 2.31 g NaCl/kg and 2.89 g NaCl/kg soil which had electrical conductivity (EC) values of 0.13 mS/cm, 0.62 mS/cm, 0.74 mS/cm, 0.95 mS/cm and 1.16 mS/cm, respectively. The addition of salt had different effects on the rice grain yield, yield component and aromatic compound, but did not affect the softness texture. Adding salt into the soil depressed the grain yield on average by 36.3% for all applications. The adverse effect of salt on the yield was correlated with the effect on the 1,000 grain weight (correlation coefficient (r) = -0.94, p < 0.05). The lowest level of salt application at 1.16 g NaCl /kg soil significantly raised the level of 2 AP, but not at the higher rates of salt application. Soil salinity did not affect the quality of grain softness texture at any application rate. These results suggested that while salinity may invariably depress the rice yield, at a certain level it may improve the grain quality by increasing the concentration of the main aromatic compound without impacting the softness texture. This needs to be confirmed using field trials in naturally occurring saline soils.